2020
DOI: 10.1371/journal.pone.0228989
|View full text |Cite
|
Sign up to set email alerts
|

Urinary chemical fingerprint left behind by repeated NSAID administration: Discovery of putative biomarkers using artificial intelligence

Abstract: Prediction and early detection of kidney damage induced by nonsteroidal anti-inflammatories (NSAIDs) would provide the best chances of maximizing the anti-inflammatory effects while minimizing the risk of kidney damage. Unfortunately, biomarkers for detecting NSAIDinduced kidney damage in cats remain to be discovered. To identify potential urinary biomarkers for monitoring NSAID-based treatments, we applied an untargeted metabolomics approach to urine collected from cats treated repeatedly with meloxicam or sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…ROC‐curve biomarker analysis is generally considered the best method for developing and assessing the performance of medical diagnostic tests (Xia et al, 2013). In order to minimize the likelihood of capturing irrelevant substances, the selection of potential biomarkers can be rigorously scrutinized by applying a combination of statistical tests such as the receiver operating characteristic curve, random forest, and PLS‐DA analyses (Broughton‐Neiswanger et al, 2020; Rivera‐Velez, Broughton‐Neiswanger, Suarez, Pinñyro, et al, 2019, Rivera‐Velez, Broughton‐Neiswanger, Suarez, Slovak, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ROC‐curve biomarker analysis is generally considered the best method for developing and assessing the performance of medical diagnostic tests (Xia et al, 2013). In order to minimize the likelihood of capturing irrelevant substances, the selection of potential biomarkers can be rigorously scrutinized by applying a combination of statistical tests such as the receiver operating characteristic curve, random forest, and PLS‐DA analyses (Broughton‐Neiswanger et al, 2020; Rivera‐Velez, Broughton‐Neiswanger, Suarez, Pinñyro, et al, 2019, Rivera‐Velez, Broughton‐Neiswanger, Suarez, Slovak, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple validations models which are shown in Figure 3. The external validation method requires partitioning the data into a training set used to build a model, and a validation set used to assess the predictive ability of the model, where the validation set is in no way used to generate the trained model (Broughton‐Neiswanger et al, 2020; Chan et al, 2011; Worley, & Powers, 2013). This validation method should only be applied if enough individuals are available to build a reliable model (Triba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If this is the case, some of the organic acids identified in this study could serve as biomarkers for monitoring nepphrotoxicity of meloxicam in cats. A recently published companion manuscript showed that changes in serum creatinine took 9 days to become elevated following meloxicam administration (Broughton‐Neiswanger et al., 2020). By comparison, the panel of metabolites described here distinguished meloxicam‐treated cats from saline‐treated control cats after 2 days of meloxicam administration in the testing data set of cats.…”
Section: Discussionmentioning
confidence: 99%